2021
DOI: 10.3389/fmicb.2021.682437
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Fengycin and Iturin A Isolated From Bacillus subtilis Z-14 on Gaeumannomyces graminis Var. tritici and Soil Microbial Diversity

Abstract: Bacillus subtilis Z-14 can inhibit phytopathogenic fungi, and is used as a biocontrol agent for wheat take-all disease. The present study used the soil-borne fungus Gaeumannomyces graminis var. tritici (Ggt), which causes wheat take-all disease, and the soil microbial community as indicators, and investigated the antifungal effects of fengycin and iturin A purified from strain Z-14 using high performance liquid chromatography and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 60 publications
(73 reference statements)
1
34
0
Order By: Relevance
“…The treated cells looked deformed with loss of cellular integrity and budding capability, indicating that cell membrane disruption and division impairment are major mechanisms of action of the K7 bioactive metabolites, consistent with previous reports of anticandidal action of lipopeptides (Sharma et al 2020). The presence of multiple 'empty' CA cells, devoid of any discernible cellular material in the K7 extract-treated set suggests the destruction of the cell membranes, a typical feature of antimicrobial biosurfactant molecules (Xiao et al 2021).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The treated cells looked deformed with loss of cellular integrity and budding capability, indicating that cell membrane disruption and division impairment are major mechanisms of action of the K7 bioactive metabolites, consistent with previous reports of anticandidal action of lipopeptides (Sharma et al 2020). The presence of multiple 'empty' CA cells, devoid of any discernible cellular material in the K7 extract-treated set suggests the destruction of the cell membranes, a typical feature of antimicrobial biosurfactant molecules (Xiao et al 2021).…”
Section: Resultssupporting
confidence: 87%
“…The presence of multiple ‘empty’ CA cells, devoid of any discernible cellular material in the K7 extract‐treated set suggests the destruction of the cell membranes, a typical feature of antimicrobial biosurfactant molecules (Xiao et al . 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the secretome of the B. subtilis strain 168 has been studied extensively for its ability to produce many compounds that are beneficial for industry [ 29 , 47 , 48 ]. In addition, treatment of CFS with heat and proteinase K did not decrease the activity of the CFS against Fg -K1-4 indicating that the antagonistic compounds are thermostable and not proteinaceous but possibly antimicrobial compounds such as fengycin and iturin A [ 49 ]. In other studies where compounds were purified, the minimal inhibitory concentrations were found to be in the range of 50 to 128 µg/mL for iturin A and fengycin A [ 24 , 45 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fengycins are lipopeptides produced by Bacillus spp. that display potent antifungal activity against plant pathogens and multidrug-resistant foodborne pathogens 18 , 19 . This compound has great potential for application as a biocontrol agent in the agriculture and food industries.…”
Section: Discussionmentioning
confidence: 99%